Impact of Video-Based Aerobic Dance on Higher Students' Endurance and Concentration - Arfanda, Poppy Elisano; Aprilo, Ians; Arimbi, Arimbi; Hasanuddin, M. Imran; Nurulita, Retno Farhana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The objective of this study is to evaluate the effectiveness of a video-based aerobic dance program in improving students' cardiorespiratory endurance and concentration. The background of this study is based on the need to develop a flexible and adaptive physical exercise model in the digital era, especially to overcome sedentary lifestyles and cognitive decline among students. The research design used was a quasi-experimental study with a one-group pretest-posttest approach. The sample consisted of 20 students participating in the video-based aerobic dance program for six weeks, three times a week. The instruments used included the Beep Test to measure VO₂ max capacity and the Grid Concentration test to measure concentration. The results of the analysis showed a significant increase in both variables, with a significant value in the paired sample t-test of 0.00 (p < 0.05). This study concludes that video-based aerobic dance is effective in improving cardiorespiratory endurance and concentration of students and can be used as an alternative, innovative, and adaptive exercise in higher education environments.